SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PERUMAHAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Hartika Manao; Berto Nadeak; Taronisokhi Zebua (STMIK Budi Darma, 2017)
Housing is a basic human need and needs to be nurtured and developed for the sake of the continuity and improvement of people's lives and settlements that can not be seen as a means of necessity solely, but more than that is the process of human settlements in creating a space of life to socialize themselves in expressing their identity. During this time customers make housing selection based on information from others, observing housing and experience by not considering the criteria needed so often cause new problems for the customer after buying housing. Problems such as inconvenience, credit installment problems and so forth. Decision support systems are generally defined as a system capable of producing solutions and problem- solving. Decision support systems are not intended to replace decision-making roles, but to assist and support decision makers. One of the most commonly used methods in decision support systems is the simple additive weighting (SAW) method. This simple additive weighting method can determine the preference value of each alternative, then perform the warfare process that can select the best alternative from a number of alternatives available.